Determine the optimal decision in the process of production planning usingDynamic programming style - بخيت عبد الجبار خضر; بطيخ عباس حسين; عطا خالد وليد (Journal of Economics and Administrative Sciences, 2009)
The operation of production planning is a difficult operation and it’s required High effect and large time especially it is dynamic activity which it’s basic variables change in continuous with the time, for this reason it needs using one of the operation research manner (Dynamic programming) which has a force in the decision making process in the planning and control on the production and its direct affect on the cost of production operation and control on the inventory.